Живая шляпа: рассказы / Н.Н. Носов; ил. И. Семенова - Носов Николай Николаевич (Книги-мои друзья, 2012)
Экземпляры: М/а ДБ (20150318) / Инвентарный номер: 102342 / Цена: 95.00 / Авт.знак: Н 84 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6